Lg(5y²-2y+1)/3lg(4y²-5y+1)≤1/3*log(5)7/log(5)7
lg(5y²-2y+1)/lg(4y²-5y+1)≤1
ОДЗ
5y²-2y+1gt;0
D=4-20=-18lt;0,agt;0⇒y∈(-∞;∞)
4y²-5y+1gt;0
D=25-16=9
y1=(5-3)/8=1/4
y2=(5+3)/8=1
ylt;1/4 U ygt;1
lg(4y²-5y+1)≠0
4y²-5y+1≠1
4y²-5y≠0
y(4y-5)≠0
y≠0 U y≠5/4
y∈(-∞;0) U (0;1/4) U (1;5/4) U (5/4;∞)
log(5y²-2y+1)/lg(4y²-5y+1) -1≤0
[lg(5y²-2y+1)-lg(4y²-5y+1)]/lg(4y²-5y+1)≤0
lg[(5y²-2y+1)/(4y²-5y+1)]/lg(4y²-5y+1)≤0
a){lg[(5y²-2y+1)/(4y²-5y+1)]≥0 (1)
{lg(4y²-5y+1)lt;0 (2)
(1)(5y²-2y+1)/(4y²-5y+1)≥1
(5y²-2y+1)/(4y²-5y+1) -1≥0
(5y²-2y+1-4y²+5y-1)/(4y²-5y+1)≥0
(y²+3y)/(4y²-5y+1)≥0
y(y+3)/[4(y-1/4)(y-1)≥0
y=0 y=-3 y=1/4 y=1
+ _ + _ +
-----------[-3]------------[0]-----------(1/4)----------(1)----------
y≤-3 U 0 ≤ ylt;1/4 U ygt;1
(2)lg(4y²-5y+1)lt;0
4y²-5y+1lt;1
4y²-5ylt;0
y(4y-5)lt;0
y=0 y=5/4
0lt;ylt;5/4
y∈(0;1/4) U (1;5/4)
б){lg[(5y²-2y+1)/(4y²-5y+1)]≤0 (3)
{lg(4y²-5y+1)gt;0 (4)
(3)-3≤y≤0 U 1/4lt;ylt;1
(4)ylt;0 U ygt;5/4
y∈[-3;0)
Ответ y∈[-3;0) U (0;1/4) U (1;5/4)